INCREASING THE VOCATIONAL STUDENTS' ABILITY IN MATHEMATICAL UNDERSTANDING BY APPLYING PROBLEM BASED LEARNING AND TEAM GAMES TOURNAMENT MODEL - Sur Rasyid (USN Kolaka, 2017)
The students' understanding ability is still relatively low, caused by the quality of mathematics learning in the classroom, so students feel bored in learning mathematics, passive students in learning, students are not independent in constructing knowledge and students are not trained to develop the ability to think. Learning model that is expected to be good for applied to learning mathematics and in order to encourage the emergence of students' understanding in mathematics is Problem Based Learning and Teams Games Tournament model. The purpose of this study is to improve the students' understanding in mathematics through the application of Problem Based Learning and Teams Games Tournament Model. This research is experimental research with preetest-postest design group design. The population of this study is all students of class XI SMKN 4 Kendari, the research sample taken two classes with purposive sampling technique and the determination of experimental class and control class chosen at random. First experimental class got model of Problem Based Learning Learning (PBL) and second experiment class got cooperative learning model Type Teams Games Tournament (TGT). The research instrument used is pretest and postes Mathematical Understanding. The data obtained were analyzed descriptively qualitative and t-test. Based on the results in data analysis can be concluded that: 1) There is improvement of students' understanding in mathematics through PBL model .2) There is an improvement in students' mathematical understanding through TGT model. 3) There is a difference in students' mathematical understanding improvement among those taught by PBL and TGT model.